Portrait of literary works by Riau Authors using a knowledge graph - Tiara Yusrianda; Nining Sudiar; Winda Monika; Arbi Haza Nasution (Berkala Ilmu Perpustakaan dan Informasi)
Introduction. The literary works produced by Riau authors are generally documented in unstructured text formats, making it difficult to organize, search, and access information efficiently. This study aims to visualize literary works through the implementation of a knowledge graph to provide more structured and integrated access to literary information.